Estrategias lúdicas en la resolución de operaciones básica - Sarmiento Guadalima, Marycarmen (2023)
The following research on ludic strategies for resolving basic operations has as a general objective to determine the incidence of ludic strategies in the resolution of basic operations in the fourth grade of primary school "Pompilio Reinoso Jaramillo"; three specific objectives were developed, the first one focused on diagnosing the level of resolution of basic operations, the second one on proposing an improvement proposal using ludic strategies to strengthen basic operations and the third objective focused on evaluate the incidence of ludic strategies in the resolution of basic operations. Additionally a descriptive approach and non-experimental design for this study was applied, with methods ranging from analytical to observational to descriptive to hermeneutical to statistical to carry out the study. As for the techniques employed, an interview, pre-evaluation, and post-evaluation questionnaires were utilized, as were the instruments used during pre-evaluation and post-evaluation. Using a non-probabilistic sampling, 25 students and one teacher were selected from the school "Pompilio Reinoso Jaramillo".It is important to mention that the results of the research indicate that the students present notorious difficulties at the time of performing basic operations; It is fundamental that in order to acquire significant knowledge it is necessary to implement innovative methodologies, for this reason, an activity guide was designed to improve the teaching and learning process of the students. Key words: Playfulness, teaching, learning, methodologies, basic operations.